ALAT KENDALI KECEPATAN MOTOR PADA PENGGERAK DEPAN SEPEDA LISTRIK DI POLITEKNIK NEGERI BATAM - Qoriatul Fitriyah; Renaldy Aritha; Handri Toar; Muhammad Prihadi Eko Wahyudi (JURNAL INTEGRASI, 2020)
Brushless DC motor is applied in many field of industries, one of which transportation sector. The operation of BLDC motor need a speed control system as commutation process since it does not applied any brush. This research using an Arduino nano as its microcontroller to regulate the switching driver mosfet with IR2103 type. This mosfet driver is used to trigger mosfet switching at iverter 3 phase circuit so that power from battery can flow to BLDC motor. Mosfet type is STP75NF75 with Vds 75 Volt and Ids 80 Amps, while type of motor used is BLDC 350 watt and 36 Volt. The BLDC motor has Hall Effect sensor as rotor positioning detection. As for the commutation process, PWM is used as pulse modulation which is represented the motor speed and frequency of PIN default of Arduino. Speed earned is 224-340 rpm with power consumption of 20-21 Watts.